THE EFFECT OF CURRENT RATIO, RETURN ON EQUITY, AND DEBT TO EQUITY RATIO ON STOCK RETURNS ON THE INDONESIA STOCK EXCHANGE - Maria Cendiviani Ojo; Redy Herinanto Albertus (UPMI Management, 2021)
This research examined the effect of the Current Ratio, Return on Equity, and Debt to Equity Ratio on Stock Returns in Kompas 100 Companies Listed on the Indonesia Stock Exchange in the 2015-2019 period. The sampling technique used in this study was purposive sampling. The samples obtained were 30 companies from 100 companies. The type of data used in this research is secondary data, and the method of analysis uses multiple linear regression analysis. Based on the data analysis done, the variable Return on Equity has a positive and significant effect on stock returns. The Current Ratio has a negative and insignificant effect on stock returns, and the Debt to Equity Ratio has a negative and insignificant effect on stock returns. The current ratio, return on equity, and debt to equity ratio simultaneously does not affect stock returns.